Menciptakan Sekolah Berkarakter - Elim Halimatusadiyah (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Character education is a central issue in Indonesian society, addressing concerns about educational inequality and the behavior of graduates. This article explores these issues and the diverse interpretations of the concept of "character education." Character, in linguistic and cultural contexts, is defined as fundamental traits, personality, and habits shaping behavioral patterns. Character education, involving religious, social, and cultural dimensions, aims to form virtues in thoughts, attitudes, and daily behavior. Schools, as formal educational institutions, play a crucial role in shaping students' characters. With a focus on cleanliness, discipline, and politeness, character-based schools are seen as creating a conducive educational environment. The research method employed is a literature review, gathering information from various sources. The findings emphasize the importance of a clear understanding of character education to address educational issues and build a solid moral foundation for future generations